Low-carbohydrate training increases protein requirements of endurance athletes - Gillen, J. B.; West, D. W.; Williamson, E. P.; Fung, H. J. W.; Moore, D. R. (Medicine & Science in Sports & Exercise, 2019)
INTRODUCTION: Training with low-carbohydrate (CHO) availability enhances markers of aerobic adaptation and has become popular to periodize throughout an endurance-training program. However, exercise-induced amino acid oxidation is increased with low muscle glycogen, which may limit substrate availability for postexercise protein synthesis. We aimed to determine the impact of training with low-CHO availability on estimates of dietary protein requirements.